Kontribusi VO2 Max terhadap Kemampuan Renang Gaya Dada 200 Meter - Erick Salman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study is to see the contribution of VO2 Max to the ability of breaststroke pool 200 M. This type of research is correlational is to see the contribution of VO2 Max to the ability of breaststroke pool 200 M. The population in this study are students of the Department of Health and Recreation Faculty of Sport Sciences University Negeri Padang in 2013 that took the swimming course totaling 112 people. Sampling technique in this research is random sampling taken 50 percent in each of the code section with the total sample result all 54 people. The data was collected by carrying out the VO2 Max test and a 200 meter breaststroke capability test. Data analysis and hypothesis testing research using simple correlation analysis technique with significant level α = 0,05. To find contributions using the formula r2 x 100 percent. Based on the results of the study, it can be seen the comparison of r count 0.382 greater than r table 0.261 then the data shows there is a relationship between VO2 Max with 200 meter breaststroke ability and also tcount 3.24 greater than ttab 1,675 showed a significant relationship between VO2 Max and a 200 meter breaststroke ability. Based on the results of the study showed the contribution of VO2 Max to the 200 meter breaststroke proficiency of the students of Department of Health Recreation FIK UNP with the percentage of 14.59 percent. Keywords: Pool Style Chest, VO2 Max